Chronic Pain Patients’ Gaze Patterns toward Pain-Related Information: Comparison between Pictorial and Linguistic Stimuli - Jieun Lee; Jaewon Beom; Seoyun Choi; Seulgi Lee Amy Wachholtz; Jang-Han Lee (Medicina, 2019)
Background and Objectives: The attentional bias and information processing model explained that individuals who interpret pain stimuli as threatening may increase their attention toward pain-related information. Previous eye tracking studies found pain attentional bias among individuals with chronic pain; however, those studies investigated this phenomenon by using only one stimulus modality. Therefore, the present study investigated attentional engagement to pain-related information and the role of pain catastrophizing on pain attentional engagement to pain-related stimuli among chronic pain patients by utilizing both linguistic and visual stimulus. Materials and Methods: Forty chronic pain patients were recruited from the rehabilitation center, the back pain clinic, and the rheumatology department of Chung-Ang University Hospital in Seoul, Korea. Patients observed pictures of faces and words displaying pain, presented simultaneously with neutral expressions, while their eye movements were measured using the eye tracking system. A t-test and ANOVA were conducted to compare stimulus pairs for the total gaze duration. Results: Results revealed that chronic pain patients demonstrated attentional preference toward pain words but not for pain faces. An ANOVA with bias scores was conducted to investigate the role of pain catastrophizing on attentional patterns. Results indicated that chronic pain patients with high pain catastrophizing scores gazed significantly longer at pain- and anger-related words than neutral words compared to those with low pain catastrophizing scores. The same patterns were not observed for the facial expression stimulus pairs. Conclusions: The results of the present study revealed attentional preference toward pain-related words and the significant role of pain catastrophizing on pain attentional engagement to pain-related words. However, different patterns were observed between linguistic and visual stimuli. Clinical implications related to use in pain treatment and future research suggestions are discussed.